A Chinese version of the Psychotic Symptom Rating Scales: psychometric properties in recent-onset and chronic psychosis - Chien WT (Dove Medical Press, 2017)
Wai-Tong Chien,1 Isabella Yuet-Ming Lee,2 Li-Qun Wang3 1School of Nursing, Faculty of Health and Social Sciences, The Hong Kong Polytechnic University, Hung Hom, Kowloon, Hong Kong, People’s Republic of China; 2Central Nursing Division, Ruttonjee Tang Shiu King Hospital, Wan Chai, Hong Kong, People’s Republic of China; 3School of Nursing, Jilin Medical College, Jilin City, Jilin Province, People’s Republic of China Abstract: The purpose of this study was to test the reliability, validity, and factor structure of a Chinese version of the Psychotic Symptom Rating Scale (PSYRATS) in 198 and 202 adult patients with recent-onset and chronic psychosis, respectively. The PSYRATS has been translated into different language versions and has been validated for clinical and research use mainly in chronic psychotic patients but not in recent-onset psychosis patients or in Chinese populations. The psychometric analysis of the translated Chinese version included assessment of its content validity, semantic equivalence, interrater and test–retest reliability, reproducibility, sensitivity to changes in psychotic symptoms, internal consistency, concurrent validity (compared to a valid psychotic symptom scale), and factor structure. The Chinese version demonstrated very satisfactory content validity as rated by an expert panel, good semantic equivalence with the original version, and high interrater and test–retest (at 2-week interval) reliability. It also indicated very good reproducibility of and sensitivity to changes in psychotic symptoms in line with the symptom severity measured with the Positive and Negative Syndrome Scale (PANSS). The scale consisted of four factors for the hallucination subscale and two factors for the delusion subscale, explaining about 80% of the total variance of the construct, indicating satisfactory correlations between the hallucination and delusion factors themselves, between items, factors, subscales, and overall scale, and between factors and relevant item and subscale scores of the PANSS. The Chinese version of the PSYRATS is a reliable and valid instrument to measure symptom severity in Chinese psychotic patients complementary to other existing measures mainly in English language. Keywords: delusion, hallucination, psychosis, PSYRATS, reliability, validity